Properties of Alanine Dehydrogenase and Aspartase from Propionibacterium freudenreichii subsp. shermanii - Crow, Vaughan L. (1987)
During lactate fermentation by Propionibacterium freudenreichii subsp. shermanii ATCC 9614, the only amino acid metabolized was aspartate. After lactate exhaustion, alanine was one of the two amino acids to be metabolized. For every 3 mol of alanine metabolized, 2 mol of propionate, 1 mol each of acetate and CO(2), and 3 mol of ammonia were formed. The specific activity of alanine dehydrogenase was 0.08 U/mg of protein during lactate fermentation, and it increased to 0.9 U/mg of protein after lactate exhaustion. Alanine dehydrogenase and aspartase, key enzymes in the metabolism of alanine and aspartate, respectively, were partially purified, and some of their properties were studied. Alanine dehydrogenase had a pH optimum of 9.2 to 9.6 and high K(m) values for both NAD(+) (1 to 4 mM) and alanine (7 to 20 mM). Activity was inhibited by low concentrations of pyruvate and NADH. The pH optimum of aspartase decreased from ∼7.5 to ∼6.4 when the MgCl(2) and aspartate concentrations were decreased. Plots of aspartate concentration versus activity showed either hyperbolic or sigmoidal kinetics (interaction coefficient, up to a value of 3.1), depending on pH and MgCl(2) concentration. MgCl(2) was either an activator or an inhibitor, depending on pH and its concentration. Aspartase activity was inhibited by low concentrations of fumarate. The properties of alanine dehydrogenase and aspartase are consistent with the finding that aspartate is metabolized during lactate fermentation, while alanine is only fermented after lactate exhaustion and then at a slow rate.